Evolución de la acidez en un ultisol a la aplicación de cal y respuesta en la fase inicial del cultivo del café (Coffea arabica L.) en pueblo nuevo del cantón Loja - Rodríguez Sarango, Rosa del Cisne (2019)
Coffee cultivation is one of the main agricultural activities is done in Ecuador, the Arabica coffee species occupies 65% of the national coffee production, with a productivity of 0.49 t ha-1. Low productivity is a problem in the province of Loja with an Arabica coffee yield of 0.32 t ha-1 and in the Loja canton with a yield of 0.17 t ha-1, lower than other provinces such as Carchi with 0.93 t ha-1. The main limiting factor in agricultural production is caused by acidity due to the variety of parental materials and environmental conditions where they developed, so a vast area is covered by old soils (ultisols), therefore, it is necessary to control acidity to rise and sustain good agricultural yields. The present investigation was done by the rapid incubation method consisted of the application of calcium hydroxide Ca (OH)2 based on the exchangeable content of Al+3: 0.0, 1.0, 1.5, 2.0 and 2.5 cmol (+) kg-1, the pH and Al+3 were evaluated every 24, 48, 72, 96 and 120 hours. The best treatments were 2 cmol (+) kg-1 and 2.5 cmol (+) kg-1 of soil, rising the pH from 4.6 to 5.1 and 5.3, respectively; and a reduction of Al+3 from 2.1 cmol (+) kg-1 to 1.2 cmol (+) kg-1. The treatments of 2 cmol (+) kg-1 and 2.5 cmol (+) kg-1 correspond to 5.0 and 6.3 t ha-1 of agricultural lime, respectively. All experimental units got N, P, K, B, Mg and Zn in the initial stage of coffee cultivation. At 120 days after the application of agricultural lime there was a significant increase in the pH from acid to moderately acidic; Al+3 reduced from very toxic to low, and the percentage of base saturation went from high to very high. Plant height, basal diameter, cup diameter and number of leaves there was a significant increase. Keywords: acidity, incubation, agricultural lime and coffee